Carbon, land and water: a global analysis of the hydrologic dimensions of climate change mitigation through afforestation / reforestation - Zomer, Robert J.; Trabucco, Antonio; Straaten, Oliver van; Bossio, Deborah A. (International Water Management Institute, 2006)
This report highlights the potentially significant impacts on the hydrologic cycle and the importance of considering secondary effects, particularly with regard to water, resulting from the widespread adoption of global climate change mitigation measures. It is recommended that the implicit hydrologic dimensions of climate change mitigation should be more formally articulated within the international environmental conventions, and recognized within future UNFCCC negotiations on the CDM-AR provisions.